(untitled) (Вестник КазНУ. Серия Востоковедения, 2018)
The article is devoted to communicative and pragmatic features of diplomatic papers. In this article, the analysis of the communicative and pragmatic specifics of Arab diplomatic papers was carried out for the first time, aimed at revealing their specific integrants. The study is conducted through consideration of lexical and syntactic problems of diplomatic correspondence. As a result of the research, it was possible to show for the first time the reality of the communicative-pragmatic specifics and the structural differentiation of the functional-communicative syntax of Arab diplomatic papers caused by it. The pragmatics of informing the genre of a verbal note finds its expression in the definition of the space-time relationship (chronotope) of participants in the diplomatic discourse (addressee and addressee) and the object under discussion. It is proved that the verb plays a basic role in the indication of the time of diplomatic discourse. In addition to verbs, accurate time indicators are actively used in the texts of verbal notes, such as indicating the number, month and year, which indicates the institutional nature of the genre. The indication of exact dates (date - date, day of the week, month, year) reflects a prospective character; interaction of communicants. In this paper, an attempt was made to analyze the linguopragmatic characteristics of diplomatic discourse from the perspective of pragmalinguistics and discursive analysis. This study is a step towards further research of the discursive genre of written diplomatic communication as a promising subject of linguistic analysis.